Review on “Ottapparu – an Account on Diabetic Abscess” - Akhila, C; Binitha, A (International Research Journal of Ayurveda & Yoga, 2022)
Prevalence of diabetes and its complications have been a burden to society from ancient times, in the present and will also be in the future unless proper measures are taken to prevent its manifestation. There have been an increasing number of deaths associated-amputation cases which are mainly caused by non healing wounds. Even with the latest technology and modern medicine with a highly trained medical team around, yet the majority of the diabetic ulcers end up with more or less amputation of the concerned major or minor part of the lower limb.